PENGARUH SISTEM PENGELOLAAN KEARSIPAN TERHADAP PELAKSANAAN PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) DIKANTOR KECAMATAN BANYUURIP KABUPATEN PURWOREJO - Safridha Oktavia SR (STIE Rajawali Purworejo, 2022)
This research aims to determine the influence of the records management system on the implementation of good government at the Banyuurip District Office, Purworejo Regency. The research method used in this research is a quantitative research method with data collection techniques through observation, interviews, questionnaires, documentation and literature study. Research data was obtained from 24 respondents who were also samples in this study, all of whom were employees at the Banyuurip District office. Furthermore, the data obtained in this research was analyzed using Simple Correlation Coefficient Analysis, Simple Regression Analysis, Determination Analysis, and T Test. The results of this research show that the correlation coefficient of the records management system is in the interval 0.60-0.799, meaning the level of relationship between these variables strong. . This means that the better the records management system, the better the implementation of good governance. Based on simple linear regression calculations, the regression equation Y= 19.688 + 0.536 (X) is obtained. The result of the constant coefficient is 19.688 on the value of the records management system variable (X), so the level of implementation of good governance is 0.536. The coefficient of determination seen from R Square is 0.524, this means that the contribution of the archive management system variable (X) to the implementation of good governance variable (Y) is 52.4% while the remaining is 47.6%. The results of the t-test calculation show that the t-table value is greater than the t-count, so that the working hypothesis (Ha) which states that partially there is a positive and significant influence between the records management system variable (X) on the good governance implementation variable (Y) is accepted. , and the null hypothesis (H0) which states that partially there is no positive and significant influence between the archive management system variable (X) on the implementation of good governance variable (Y) is rejected. This shows the influence of the records management system in implementing good governance in the Banyuurip District Office, Purworejo Regency.